Radiotherapy in the treatment of aggressive fibromatosis: experience from a single institution - Seidensaal, Katharina; Harrabi, Semi B.; Weykamp, Fabian; Herfarth, Klaus; Welzel, Thomas; Mechtersheimer, Gunhild; Lehner, Burkhard; Schneider, Martin; Fröhling, Stefan; Egerer, Gerlinde; Debus, Jürgen; Uhl, Matthias (Radiation oncology, 2020)
Desmoid-type fibromatosis is a rare, potentially locally aggressive disease. Herein we present our experience in the treatment with radiotherapy.